2023
DOI: 10.4252/wjsc.v15.i6.548
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting osteogenesis and chondrogenic differentiation of mesenchymal stem cells in osteoarthritis

Abstract: Osteoarthritis (OA) is a common degenerative joint disease that often involves progressive cartilage degeneration and bone destruction of subchondral bone. At present, clinical treatment is mainly for pain relief, and there are no effective methods to delay the progression of the disease. When this disease progresses to the advanced stage, the only treatment option for most patients is total knee replacement surgery, which causes patients great pain and anxiety. As a type of stem cell, mesenchymal stem cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 125 publications
0
3
0
2
Order By: Relevance
“…Among them, Dex stands out as a glucocorticoid anti-inflammatory drug with clinical applications in knee OA treatment. It offers short-term pain relief and functional improvement, but prolonged use may entail specific side effects and potentially exacerbate OA symptoms [ 33 ]. Estradiol, an estrogen variant, exhibits associations with structural changes linked to knee OA in women.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, Dex stands out as a glucocorticoid anti-inflammatory drug with clinical applications in knee OA treatment. It offers short-term pain relief and functional improvement, but prolonged use may entail specific side effects and potentially exacerbate OA symptoms [ 33 ]. Estradiol, an estrogen variant, exhibits associations with structural changes linked to knee OA in women.…”
Section: Discussionmentioning
confidence: 99%
“…Mélou et al, using adult dental pulp MSCs, demonstrated that a spheroid model ensures higher expression of chondrogenesis markers compared to monolayer or pellet culture [ 21 ]. By reviewing the reported clinical trials, Peng et al found that osteoarthritis cell-based therapy translational research is mostly limited to bone marrow-derived MSCs (BMMSCs), ATMSCs, and WJMSCs [ 22 ]. BMMSCs are known to have high chondrogenic potential and are efficient in the stimulation of articular cartilage regeneration [ 23 ], but the harvesting of MSCs from bone marrow is an invasive procedure prone to complications.…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone was previously found to promote MSC chondrogenic differentiation [32], a process reportedly suppressed in dexamethasone-free cultures [33] acting by increasing proteoglycan and collagen type II content. Dexamethasone may act as a promoter of key masters of differentiation (such as Runx2 and Noggin) in a context-dependent manner [34]. In the case where ADSCs were preconditioned with MNEs, significantly higher chondrogenesis was detected for both MNEs cargo types compared to non-treated controls.…”
Section: Discussionmentioning
confidence: 99%